2008
DOI: 10.1146/annurev.earth.36.031207.124139
|View full text |Cite
|
Sign up to set email alerts
|

The Iron Isotope Fingerprints of Redox and Biogeochemical Cycling in Modern and Ancient Earth

Abstract: The largest Fe isotope fractionations occur during redox changes, as well as differences in bonding, but these are expressed only in natural environments in which significant quantities of Fe may be mobilized and separated. At the circumneutral pH of most low-temperature aqueous systems, Fe 2+ aq is the most common species for mobilizing Fe, and Fe 2+ aq has low 56 Fe/ 54 Fe ratios relative to Fe 3+-bearing minerals. Of the variety of abiologic and biologic processes that involve redox or bonding changes, micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
290
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 419 publications
(302 citation statements)
references
References 144 publications
10
290
1
1
Order By: Relevance
“…Carbon isotope evidence suggests life arose before Ϸ3.8 Ga (36, 37) and the presence of several prokaryotic groups in the Archean including sulfate reducers (38), sulfurdisproportionaters (39), iron reducers (15,40), and methanogens (8, 41) have been proposed. Carbon isotopic evidence also indicates that a significant global methane cycle developed by the late Archean, indicating a growing ecological role for methanogens during this eon (42).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon isotope evidence suggests life arose before Ϸ3.8 Ga (36, 37) and the presence of several prokaryotic groups in the Archean including sulfate reducers (38), sulfurdisproportionaters (39), iron reducers (15,40), and methanogens (8, 41) have been proposed. Carbon isotopic evidence also indicates that a significant global methane cycle developed by the late Archean, indicating a growing ecological role for methanogens during this eon (42).…”
Section: Resultsmentioning
confidence: 99%
“…An array of tools has traditionally been harnessed, including organic molecules (12) and the isotopic composition of key bioactive elements whose surface geochemical cycles are dominated by the biosphere (13). The transition metals are a recent addition to the latter group, with Fe undergoing the most intensive study (14,15). Fe has advantages and disadvantages in this regard, as the many studies conducted on its isotope system have shown.…”
mentioning
confidence: 99%
“…25). Measurements of DFe redox speciation (DFe II and total DFe from which DFe III can be computed) during the BGH cruise provide the opportunity to evaluate the effect of the iron redox state on its isotope signature in the open ocean.…”
Section: Discussionmentioning
confidence: 99%
“…Isotopic compositions of iron and sulphur in pyrites from sedimentary rocks have been proposed as potential proxies to assess the redox state of ancient oceans (Rouxel et al, 2005;Reinhard et al, 2009;Marin-Carbonne et al, 2014), the oxygen outgrowth in the atmosphere (Catling and Claire, 2005;Ohmoto et al, 2006) and early microbial metabolisms (Johnson et al, 2008). Moreover, trace metals incorporated in pyrite have been recognised as proxies for ancient ocean chemistry (Large et al, 2017).…”
Section: Introductionmentioning
confidence: 99%